Colonization and Investigation of Vibrio Cholera Recombination Protein in E-Coli - Heidary, Somayyeh; Yaghoubi Nezhad, Amir; Mehrabi Far, Atefeh (International Journal of Engineering and Technology, 2018)
Background and aim: Vibrio cholerae is a gram-negative bacterial pathogen that causes diarrheal disease. One of the most pathogenic factors of V. cholerae is toxin-coregulated pili. This pilus is required as the first factor in the colonization and bacterial persistence in the small intestine. Materials and Methods: In this study, V. cholerae toxin-coregulated pili A (TCPA) gene was amplified using PCR method. The above genes were purified and then expressed by being cloned into the pGEX4T-1 plasmid. Then the recombinant plasmid structure was introduced into the E. coli bacterium. Protein production was carried out by IPTG induction and optimization of culture conditions. The recombinant proteins were purified using Glutathione S-Transferase (GST) Assay Kit and western blot test was then carried out for confirmation of recombinant protein. Protein levels were measured using Bradford protein assay. Results: The results of the present study proved the successful expression of recombinant proteins in E. coli cells. The recombinant protein was purified by affinity chromatography. The reaction pattern between these proteins and their anti-antibodies showed that these proteins have antigenic properties. Conclusion: Since it was proved that these proteins have antigenic properties in this study, they may be used as an appropriate antigen for vaccination of V. cholera.